Autentikasi Hadith-Hadith Kitab Al-Nikah Daripada Kitab Bulughul Maram Karya Al-Hafiz Ibn Hajar Al-Asqalani - Mohd Muhiden Abd Rahman; Mohd Bakhit Haji Ali (USIM Press, 2024)
Vol. 17 No. 2 (2021): Journal of Maʿālim al-Qurʾān wa al-Sunnah